Thermal conductivity enhancement of coaxial carbon@boron nitride nanotube arrays - Jing, Lin (2018)
We demonstrate the thermal conductivity enhancement of the vertically aligned carbon nanotube (CNT) arrays (from ∼15.5 to 29.5 W/mK, ∼90% increase) by encapsulating outer boron nitride nanotube (BNNT, 0.97 nm-thick with ∼3–4 walls). The heat transfer enhancement mechanism of the coaxial C@BNNT was further revealed by molecular dynamics simulations. Because of their highly coherent lattice structures, the outer BNNT serves as additional heat conducting path without impairing the thermal conductance of inner CNT. This work provides deep insights into tailoring the heat transfer of arbitrary CNT arrays and will enable their broader applications as thermal interface material.